A blended teaching and learning model for family-medicine registrar training at a South African university - Ann Z. George; Carien Lion-Cachet; Michele Torlutter; Neetha Erumeda; Deidre Pretorius (AOSIS, 2024)
Effective primary healthcare is essential in developing countries but faces several challenges, including the lack of standardised training across decentralised sites. In response to unsatisfactory registrar examination outcomes in 2013, the Department of Family Medicine at the University of the Witwatersrand in South Africa introduced a blended teaching and learning programme. The aim of the new programme was to level the playing field by providing uniform online resources on a course site on the university's learning management system. The uniform online resources would be integrated into the teaching programme. A team consisting of the registrar-training-programme coordinator, an educationalist and five family-medicine consultants from different districts began reviewing the curriculum, selecting appropriate resources and developing the course site. The blended programme was developed and implemented using a phased, participatory research action approach, including phases of evaluation and redesign. Since the implementation of the blended-learning programme in 2017, registrar outcomes have improved, but this has not been the only success attributed to the programme. The programme also resulted in an enhanced focus on teaching and learning, especially among those involved in its development. We share the lessons gleaned from our experiences, emphasising the need for adequate training and teamwork if we are to use technology appropriately and effectively to address the difficulties associated with decentralised training in developing countries.